Combining ability study over environments in dry beans (Phaseolus vulgaris L.) (SAARC Journal of Agriculture, 2014)
Combining ability study was carried out in a 10 x 10 diallel set of dry beans (Phaseolus vulgaris L.) for seed yield and its component characters. The 45 F1s generated by crossing ten diverse lines and their parents were evaluated in Randomized Block Design (RBD) in two replications at three locations during Kharif, 2008. Analysis of variance revealed that both gca and sca were influenced by environments, which suggested that studies be conducted over environments to get unbiased estimates. The sca x environment interaction was greater than gca x environment interaction for most of the traits. The relative magnitude of gca and sca variation indicated that greater magnitude of sca variances for all the traits, indicating greater importance of non additive gene action for the inheritance of these traits. SKUA-R-607 and SKUA-R-608 showed high combining ability for seed yield and yield attributing traits. The most promising crosses in order of merit for seed yield were Shalimar Rajmash 1 x SKUA-R-607, SKUA-R-608 x SKUA-R-106 and Shalimar Rajmash -1 x SKUA- R-612. These promising crosses may be improved through conventional breeding methods such as biparental mating and diallel selective meeting, thereafter followed by pedigree method of selection, so as the tight linkage, if any, may be broken and transgressive segregants may be isolated. DOI: http://dx.doi.org/10.3329/sja.v10i2.18324 SAARC J. Agri., 10(2): 61-69 (2012)